Poly(HydroxyButyrate-co-HydroxyValerate) (PHBHV) Nanocarriers for Silymarin Release as Adjuvant Therapy in Colo-rectal Cancer - Radu, Ionut-Cristian; Hudita, Ariana; Zaharia, Catalin; Stanescu, Paul O.; Vasile, Eugenia; Iovu, Horia; Stan, Miriana; Ginghina, Octav; Galateanu, Bianca; Costache, Marieta; Langguth, Peter; Tsatsakis, Aristidis; et al. (Frontiers in Pharmacology, 2017)
The aim of this study was to address one of the major challenges of the actual era of nanomedicine namely, the bioavailability of poorly water soluble drugs such as Silymarin. We developed new, biodegradable and biocompatible nanosized shuttles for Silymarin targeted delivery in colon-cancer cells. The design of these 100 nm sized carrier nanoparticles was based on natural polymers and their biological properties such as cellular uptake potential, cytotoxicity and 3D penetrability were tested using a highly malignant colon cancer cell line (HT-29) as the in vitro culture model. Comparative SEM and AFM measurements demonstrated that the Silymarin loaded PHBHV nanocarriers significantly decreased HT-29 cells viability after 6 and 24 hours of treatment. Moreover, in vivo-like toxicity studies on multicellular tumor spheroids showed that the Silymarin loaded PHBHV nanocarriers are able to penetrate 3D micro tumors and significantly reduce their size.